Janus kinases restrain chronic lymphocytic leukemia cells in patients on ibrutinib: Results of a phase II trial. (17th November 2021) - Spaner, David E.; Luo, Yuxuan; Wang, Guizhei; Gallagher, Jennifer; Tsui, Hubert; Shi, Yonghong
Abstract: Preclinical observations that killing of chronic lymphocytic leukemia (CLL) cells was dexamethasone (DEX) were enhanced by concomitant inhibition of Bruton's tyrosine kinase and janus kinases (JAKs) motivated a phase II trial to determine if clinical responses to ibrutinib could be deepened by DEX and the JAK inhibitor ruxolitinib. Patients on ibrutinib at 420 mg daily for 2 months or with abnormal serum β2M levels after 6 months or with persistent lymphadenopathy or splenomegaly after 12 months were randomized to receive DEX 40 mg on days 1–4 of a 4‐week cycle for six cycles alone (three patients) or with ruxolitinib 15 mg BID on days 1–21 of each cycle (five patients). Ruxolitinib dosing was based on a previous phase I trial. Steroid withdrawal symptoms and significantly decreased serum IgG levels occurred in all patients regardless of their exposure to ruxolitinib. A fatal invasive fungal infection was seen in a patient taking DEX without ruxolitinib. Complete responses anticipated with addition of ruxolitinib were not seen. Gene expression studies suggested ruxolitinib had turned off interferon signaling in CLL cells and turned on genes associated with the activation of NFκB by TNF‐α. Ruxolitinib increased blood levels of TNF‐α by cycle 3 and decreased the inhibitory cytokine IL‐10. These results suggest ruxolitinib releases activating signals for CLL cells that persist in patients on ibrutinib. This inhibitory JAK signaling may contribute to the therapeutic activity of ibrutinib. Thus JAK inhibitors provide no added value with ibrutinib for disease control and should be used with caution in CLL patients. Combining glucocorticoids with ibrutinib may increase the risk of serious infects. Abstract : Ibrutinib with ruxolitinib and dexamethasone is generally well‐tolerated but provides no benefits over ibrutinib alone. Ruxolitinib blocks inhibitory signals that suppress CLL cells in patients on ibrutinib.